Identifikasi Pakan Lebah Madu Endemik Sulawesi Apis nigrocincta (Smith, 1861) - Hamsa, Hamsa; Masrianih, Masrianih; Trianto, Manap; Ashari, Abdul; Windarsih, Yulia; Nurdin, Musdalifah (Bioscientist : Jurnal Ilmiah Biologi, 2025)
The study aims to identify the main feed source for Apis nigrocincta through the analysis of polent morphology. The study uses explorative descriptive methods with qualitative and quantitative approaches. The focus of this study is the identification of feed source for endemic honeybees of Sulawesi, Apis nigrocincta through the analysis of polent morphology. Through the approach of polent morphology analysis, successfully identified 12 plant species from 9 families that could potentially be feed sources such as, Cucurbita maxima, Clematis viticella, Clematis montana, Pseuderanthemum tropurpureum, Cersicaria odorata, Solamun torvum, Solamun nigrum, Pine mercussii, Piper betle, Piper nigrum, and Galium aparine identification showed the presence of polyn diversity that supports the nutritional needs of bees, and emphasized the importance of local vegetation conservation to maintain the sustainability of the A. nigrocincta population. The results of the study showed that the polen has characteristics such as the polish unit, size, shape, shape on the P and E side, aperture type, as well as exin ornamentation. The polents collected by bees A. nigrocincta come from various types of plants, namely fruits, ornamental plants, vegetable plants, herb plants, and trees. This diversity reflects the flexibility of bees in choosing food sources based on availability in the surrounding environment. The results of the identification of the polymer samples showed that 12 species of plants that are the main feed source for A. nigrocincta bees are sourced from the polen. Each species has different flower characteristics, both in terms of shape and color. Polen diversity indicates that the environment around Jononunu Village has a rich ecosystem with different types of floweringÂ plants.